2001
DOI: 10.1046/j.1464-5491.2001.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of diabetes mellitus and glucose intolerance in a Canarian Caucasian population – comparison of the 1997 ADA and the 1985 WHO criteria. The Guía Study.

Abstract: The prevalence of diabetes mellitus and glucose intolerance in Guía is one of the highest among studied Caucasian populations. The new 1997 ADA criteria estimate a lower prevalence of diabetes. Impaired fasting glucose also had a lower prevalence than impaired glucose intolerance and the overlap of these categories was modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 19 publications
3
20
1
3
Order By: Relevance
“…The results in the present study, in which IFG and IGT were employed in healthy Japanese subjects, are consistent with the results of these previous reports. However, several studies have reported (using the 1997 ADA criteria) that both IFG and IGT were associated with an increased prevalence of cardiovascular risk factors (38)(39)(40). Using the 2003 ADA criteria for IFG, Kim et al (41) did not observe an increased prevalence of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…The results in the present study, in which IFG and IGT were employed in healthy Japanese subjects, are consistent with the results of these previous reports. However, several studies have reported (using the 1997 ADA criteria) that both IFG and IGT were associated with an increased prevalence of cardiovascular risk factors (38)(39)(40). Using the 2003 ADA criteria for IFG, Kim et al (41) did not observe an increased prevalence of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the observations of other comparisons of the ADA to WHO criteria. For example, the 10 most recent studies we identified in which the ADA criteria were compared with other criteria, the sensitivity ranged from as low as 31% in a an obese French population to as high as 79% in Canarian Caucasians (13,14,(25)(26)(27)(28)(29)(30)(31)(32) (Table 6). We identified two cut-off values (fasting plasma glucose Ն5.7 mmol/l and an HbA 1c Ն5.9%) that minimize the number of false positives and false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…De Pablos-Velasco et al (19) showed that in a Caucasian population, both IFG and IGT had higher prevalence of certain cardiovascular risk factors compared with normal glucose tolerance; and at the same time, IFG was associated with higher total-to-HDL cholesterol ratio than IGT. Among a Swedish population, Larsson et al (20) did not find differences between IFG and IGT, whereas IFG plus IGT showed higher BMI, cholesterol, and triglyceride values than IGT and higher triglyceride values than IFG.…”
Section: Research Design and Methods -This Research Was Conducted In mentioning
confidence: 99%